Surveys in social research - de Vaus D A (Jaipur Rawat, 2003)
Surveys in Social Research provides how to plan, conduct and analyse social surveys. It emphasises the links between theory and research, the logic and interpretation of statistics and the practices of social research. It also includes material on techno
Keywords: Social sciences-research